Relationship between Consumption Patterns and Nutrition Literacy with the Incidence of Undernutrition among Anemic Adolescent Girls in State Senior High Schools in Medan City - Anisah Heriani; Evawany Yunita Aritonang; Ernawati Nasution (International Journal of Health and Medicine, 2026)
Introduction: Adolescence is a critical period that requires adequate nutritional intake, yet undernutrition remains a significant public health problem among adolescent girls. Nutrition literacy and dietary consumption patterns are important factors influencing nutritional status, particularly among adolescents with anemia. This study aimed to examine the relationship between dietary consumption patterns, nutrition literacy, and undernutrition among anemic female adolescents in public senior high schools in Medan City, Indonesia. Methods: A cross-sectional observational study was conducted among 208 anemic female adolescents aged 15–18 years from six public senior high schools in Medan City, selected through cluster and proportional random sampling. Data were collected using anthropometric measurements, hemoglobin testing, a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), and a validated nutrition literacy questionnaire. Chi-square tests were used for data analysis. Results: Most participants had inadequate nutrient intake, particularly energy, protein, and carbohydrates. Poor dietary patterns were identified in 69.2% of respondents. Functional and interactive nutrition literacy were generally low, whereas critical nutrition literacy was mostly adequate. Significant associations were found between undernutrition and protein intake (p = 0.003), dietary consumption patterns (p = 0.001), and interactive nutrition literacy (p = 0.021), while other variables showed no significant relationship. Conclusion: Undernutrition among anemic adolescent girls is associated with inadequate protein intake, unhealthy dietary patterns, and low interactive nutrition literacy. School-based nutrition education is needed to improve adolescents' nutritional status.